Effect of mechanical ball milling on the electrical and powder bed properties of gas-atomized Ti–48Al–2Cr–2Nb and elucidation of the smoke mechanism in the powder bed fusion electron beam melting process - Yim, Seungkyun; Aoyagi, Kenta; Yanagihara, Keiji; Bian, Huakang; Chiba, Akihiko (Journal of materials science & technology, 2023)
•Smoke tendency of gas-atomized and ball-milled Ti–48Al–2Cr–2Nb powders was examined in powder bed fusion electron beam melting process.•Smoke of ball-milled powder was further suppressed as increasing coordination number owing to the increased possible charge transfer path.•Capacitive response of GA powder disappeared in Al-60 and WC-30 via metal–insulator transition of oxide film caused by strain and defect accumulation.•Smoke of Al-60 and WC-30 powders was further prevented owing to the formation of a percolation cluster with metal-like electrical conductivity. Smoke is unexpected powder-splashing caused by electrostatic force and is one of the main problems hindering the process stability and applicability of the powder bed fusion electron beam (PBF-EB) technology. In this study, mechanical stimulation was suggested to suppress smoke of gas-atomized (GA) Ti–48Al–2Cr–2Nb powder using Al2O3 and WC ball milling. The deformation mechanism of the GA powder depending on the ball milling media was discussed based on the developed particle morphology distribution map and contact mechanics simulation. It was revealed that the rapid decrement of flowability and packing density after WC ball milling owing to the formation of angular fragments by the brittle fracture. The variation of surface and electrical properties by mechanical stimulation was investigated via XPS, TEM, and Impedance analysis. The electrical resistivity of the ball-milled powders gradually decreased with increasing milling duration, despite the increased oxide film thickness, and the capacitive response disappeared in Al-60 and WC-30 via metal–insulator transition. This could be due to the accumulation of strain and defects on the oxide film via mechanical stimulation. The smoke mechanism of ball-milled powders was discussed based on the percolation theory. In the smoke experiment, smoke was more suppressed for WC-10 and WC-20 than that for Al-40 and Al-50, respectively, despite the longer charge dissipation time. This could be due to the high probability of contact with conductive particles. For the Al-60 and WC-30 powders, smoke was further restricted by the formation of a percolation cluster with metal-like electrical conductivity. We believe that this study will contribute to a better understanding of the smoke mechanism and process optimization of the PBF-EB.